Keterampilan Mahasiswa Trainee Departemen Front Office pada Hotel Bintang Empat di Kota Bandung - Rismawati Hidayah; Vany Octaviany (Syntax Corporation, 2023)
The Front Office Department is often avoided by trainee students during the implementation of their On The Job Training due to a lack of confidence in their skills or soft skills. This research aims to determine the quality of soft skills possessed by trainee students in the Front Office Department of four-star hotels in Bandung City and efforts to enhance them. The research method used is qualitative ethnography, involving observations and interviews with the Front Office Manager, Front Office Supervisor, and Trainee Students in three four-star hotels in Bandung: Hotel Grand Tjokro Bandung, Hotel Four Points by Sheraton Bandung, and Hotel The Jayakarta Bandung. The research findings indicate that Trainee Students possess quality soft skills as well as an understanding of soft skill components such as work ethic, politeness, teamwork, discipline, and adaptation to norms, all of which contribute to shaping individuals of high quality that can be implemented in a work environment. Effrorts to enhance the skils of trainee students can be carried out through organizing training on ethics and communication, providing positive role models, and implementing a reward system.